ANALISIS SALURAN PEMASARAN GULA AREN (Sebuah Kasus di Industri Rumah Tangga di Desa Cigemblong Kecamatan Cigemblong Kabupaten Lebak) - Lili Gojali; Aris Supriyo Wibowo; Ari Tresna Sumantri (JURNAL AGRIBISNIS TERPADU, 2015)
This research aims to know the marketing channels of Palm Sugar, knowing the functions that areperformed by each agency marketing, and to figure out the most efficient marketing channel in themarketing of Palm sugar from the Village of Cigemblong Sub-District of Cigemblong Regency ofLebak. Areas of research in the specified purpose of the Village Cigemblong and respondents takendone by stratified random marketing agencies with a method and snowball sampling. Manufacturersof as many as 28 people, merchants, merchant 2 collectors big 2 and 19 people retailers. The dataused in the form of primary data and secondary data. This research method using descriptive andquantitative methods. Results of the study showed that there were three Palm sugar marketingchannels is, Channel I : producer – merchant retailers – consumers, marketing Chanel II : producer -Middle-men – wholesalers - merchant retailer – consumer and marketing Chanel III : producer –wholesalers – consumer.